アテネパラリンピック日本代表車いすマラソン選手の低酸素トレーニングに関する事例報告 - 村木, 里志; 調, 俊太郎; 内田, 若希; 齋藤, 誠二 (障害者スポーツ科学, 2005)
The present study revealed the adaptability and potential problems of 7 days hypoxia training in Japan's representative wheelchair marathon athlete (sex: male, age: 33 years, class: T53/54) for the Athens Paralympics. The subjects performed wheelchair roller training of 20 to 40km per day under 16.5% of oxygen concentration in an artificial climatic chamber. The running velocity, stroke frequency, rate of perceived exertion (RPE), profile of mood states, respiratory frequency, arterial oxygen saturation (SpO_2), number of red cells, and hematocrit levels were measured during the hypoxia training. Under hypoxia, running velocity and SpO_2 decreased, and RPE increased, compared with a normal environment. At the latter half of the training period, however, the velocity recovered, and accumulation of fatigue was reduced, which indicated an adaptability reaction. On the other hand, some problems were found, such as difficulty of respiratory rhythm and less acclimation of the properties of the blood.